The genetic basis of sex determination in grapes - Mélanie Massonnet (Nature Portfolio, 2020)
Grapevine is one of a few ancestrally dioecious crops that are reverted to hermaphroditism during domestication. Here, the authors identify candidate genes related to male- and female-sterility in grapes and describe the genetic process that led to hermaphroditism during domestication.